Secondary Metabolites and Antioxidant Potentials of Axis Sea Bamboo (Isis hippuris) - Sayuti, Mohammad; Putri, Widya Dwi Rukmi; Yunianta, - (Dhaka University Journal of Pharmaceutical Sciences, 2019)
Secondary metabolites of the axis section (modulla skeleton) of sea bamboo (Isis hippuris) were identified by GC-MS. The dominant compounds using GC-MS in the ethanol fraction were hexanedioic acid (11.85%), acetamide (9.46%), n-hexadecanoic acid (9.22%) and thiosulfuric acid (7.22%). On the other side, the dominant compounds of the test results in the ethyl acetate fraction were 7-oxabicyclo[4.1.0] heptanes (28.27%), 1,2- benzene dicarboxylic acid (14.77%), cis-8-(N-pyrrolidyl)-(2,2,5,5-tetradeutero)bicyclo[4.3.0]nona-3,7-diene (9.98%), hexahydropyridine (7,86%). The dominant compounds of the n-hexane fraction were hexanedioic acid (41.99%), azetidine with a peak number of 40 (9.98%), 1-octadecene (8,36%). Antioxidant activities were also evaluated by DPPH scavenging assay. The ethanol, n-hexane and ethyl acetate fractions showed total flavonoid contents of 7.86% ± 0.12, 12.97% ± 0.36, 1.88% ± 0.26, respectively and the IC50 in the antioxidant assay were 480.25±74,74, 469.50±19,13, 3221.07±138,69 respectively. Dhaka Univ. J. Pharm. Sci. 18(1): 13-20, 2019 (June)